MRI-based cartilaginous acetabular coverage after open reduction for developmental dysplasia of the hip: association with hip function and a potential compensatory role in residual dysplasia - Wang, Lijuan; Wang, Guangbin (Frontiers in Pediatrics, 2025)
PurposeTo determine the value of MRI-based cartilaginous acetabular coverage in assessing postoperative hip function in patients with DDH following open reduction surgery and to explore its potential compensatory role in cases of residual dysplasia.MethodsThis retrospective study evaluated 78 hips from 59 children who had undergone open reduction for DDH. The postoperative clinical function of each hip was assessed using the modified MacKay criteria, and hips were dichotomized into a Good-Function group (Grades I and II; n = 40) and a Poor-Function group (Grades III and IV; n = 38). For all hips, radiographic (Acetabular Head Index, AHI) and MRI-based cartilaginous parameters (anterior and lateral Cartilaginous Acetabular-Head Index, A-CAHI and L-CAHI) were measured. Receiver Operating Characteristic (ROC) curve analysis was utilized to assess the diagnostic performance of these parameters in discriminating between the functional outcome groups. Furthermore, a subgroup analysis was performed on hips with Residual Acetabular Dysplasia (RAD; defined as Acetabular Index >20°) to compare imaging parameters based on functional status.ResultsThe diagnostic performance of MRI-based parameters A-CAHI and L-CAHI in discriminating between the two functional outcome groups was high, with Area Under the Curve (AUC) values of 0.893 and 0.881, respectively. A combined MRI model achieved the highest diagnostic performance (AUC = 0.918), significantly outperforming the radiographic AHI (AUC = 0.782; p = 0.002). In the subgroup analysis of hips with Residual Acetabular Dysplasia (RAD), those with satisfactory function exhibited significantly better cartilaginous coverage compared to the unsatisfactory group (p < 0.0001 for both A-CAHI and L-CAHI). Compared to non-dysplastic controls who also had good function, the RAD-Good subgroup demonstrated significantly inferior bony anatomy (e.g., mean AHI 71.88 vs. 80.42, p = 0.0030).ConclusionMRI-based assessment of cartilaginous acetabular coverage is a superior tool for evaluating functional status after DDH surgery compared to traditional radiography. Our findings demonstrate that excellent cartilage development can compensate for underlying residual bony dysplasia, playing an important role in maintaining good hip function. Therefore, incorporating MRI into the clinical assessment of this challenging patient population is valuable for guiding clinical decision-making.